2020
DOI: 10.3389/fpsyg.2019.03044
|View full text |Cite
|
Sign up to set email alerts
|

Why and When Team Reflexivity Contributes to Team Performance: A Moderated Mediation Model

Abstract: Team reflexivity has gained popularity as a phenomenon of interest in team research, but mixed theorizing around the relationship between team reflexivity and team performance indicates that the relationship is not fully understood. In an effort to improve our understanding and explain why and when team reflexivity will be conducive to team performance, we examine the role of team diversity as a possible boundary condition and of team decision quality as an explanatory mechanism. Using survey data from 82 team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 56 publications
1
16
0
1
Order By: Relevance
“…Team reflection within teams was measured using the four-item measure from Schippers et al (2007) discussing processes subscale of their reflection measure that is based on the items from Swift and West (1998) . This measure is similar to the team reflexivity measure used in Yang et al (2020) and De Jong and Elfring (2010) , which is based on the items from Carter and West (1998) . In contrast to Yang et al and De Jong and Elfring, the scale of Schippers et al omits the item on adaptation because adaption is not a part of team reflection.…”
Section: Methodsmentioning
confidence: 99%
“…Team reflection within teams was measured using the four-item measure from Schippers et al (2007) discussing processes subscale of their reflection measure that is based on the items from Swift and West (1998) . This measure is similar to the team reflexivity measure used in Yang et al (2020) and De Jong and Elfring (2010) , which is based on the items from Carter and West (1998) . In contrast to Yang et al and De Jong and Elfring, the scale of Schippers et al omits the item on adaptation because adaption is not a part of team reflection.…”
Section: Methodsmentioning
confidence: 99%
“…Schippers et al, 2014; see Figure 1 for a list of potential reflexivity tools that can be used to help counteract these three informationprocessing failures). Crucially, reflexivity has been shown to help improve team performance (Schippers et al, 2013;Gabelica et al, 2014;Konradt et al, 2016;Lyubovnikova et al, 2017;Otte et al, 2017;Yang et al, 2020) and several review articles have examined when and why reflexivity is effective (e.g., Widmer et al, 2009;Schippers et al, 2014Schippers et al, , 2018Konradt et al, 2016;Otte et al, 2018).…”
Section: Information-processing Failures During Crisis and Reflexivity As A Potential Antidotementioning
confidence: 99%
“…Reflexivity is most often studied in the context of group decision making and is most often defined as: "the extent to which group members overtly reflect upon, and communicate about the group's objectives, strategies (e.g., decision making) and processes (e.g., communication), and adapt them to current or anticipated circumstances" (West, 2000, p. 296). Prior research has shown that reflexivity helps improve team performance (Gabelica et al, 2014;Konradt et al, 2015;Lyubovnikova et al, 2017;Otte et al, 2017;Schippers et al, 2013;Yang et al, 2020) and several review articles have examined when and why reflexivity is effective (e.g., Konradt et al, 2016;Otte et al, 2018;Schippers et al, 2014;Schippers et al, 2018;Widmer et al, 2009). A reflexive decision-making process, where all relevant information is taken into account and weighted, will not guarantee an optimal outcome, but it does increase the chance that the quality of the decisions made are better.…”
Section: The Role Of Reflexivity In Optimizing Decision-makingmentioning
confidence: 99%